Peran Ibu Sebagai Pendidik Kodrati Dalam Perpektif Islam - Maryam Ismail (Jurnal Ilmiah Islamic Resources, 2023)
In general, nature means a condition that has been outlined or predestined by Allah SWT and this nature is also known as fitrah. Nature is not to be changed but maintained and used according to its purpose. The nature of women given by Allah SWT is in accordance with the guidance of Islamic teachings. So changing nature means destroying identity. This paper examines the role of women in educating children from an Islamic perspective that the role of women towards children is very large in shaping future generations. Given the large opportunities and opportunities for women to play a role in starting the education process of their children from an early age. The potential and abilities of Muslim women have a major influence on shaping the colors and patterns of generations of Muslims in the future. Because of that, as a woman, it is expected that she has affection that is manifested in the way she raises, hugs, fulfills the needs of being friends with children. So that women must strive to be smart women as a provision to educate their children. A smart mother will give birth to smart children to give birth to a great generation. So the intelligence and tenacity as well as the mother's attitude are very dominant in determining the future of the child. A mother who neglects education for her children is a mother who violates her nature.